Adiponectin in onset and progression of T2DM with cardiac dysfunction in rats. (November 2020) - Gupta, C; Bubber, P; Fahim, M; Saidullah, B; Omanwar, S
Cardiovascular disease and type 2 diabetes mellitus (T2DM) patients have low level of adiponectin, however, till now the role of adiponectin in progression of 'T2DM with cardiac dysfunction' in animal model has not been characterized. Therefore, the aim of the present study was to develop and characterize T2DM animal model with cardiac dysfunction and to study the role of cardiac adiponectin expression in cardiac dysfunction. For this, Wistar rats (M/F) were fed a high-fat diet for different time periods: 3, 4 and 5 weeks and given a single, low-dose streptozotocin (25mg/kg), intraperitoneal injection 1 week prior to the experiments. Rats in T2DM group (3 weeks) developed hyperglycaemia, hyperlipidaemia, oxidative stress with normoinsulinaemia and mild cardiac dysfunction suggesting onset of T2DM with cardiac dysfunction. Extended high-fat feeding, that is, 4 and 5 weeks induced insulin resistance accompanied with cardiac hypertrophy, cardiac dysfunction and reduced baroreflex sensitivity indicating development of T2DM with cardiac dysfunction. Cardiac adiponectin expression did not change in rats of T2DM group (3 weeks), however, it significantly decreased in rats of two T2DM groups (4 and 5 weeks) along with increased intracellular adhesion molecule-1 levels. Thus, the present study for the first time indicates that in the present T2DM animal model, as T2DM progresses cardiac adiponectin expression also decreases which might be the precipitating factor for cardiac hypertrophy and decrease in baroreflex sensitivity, which induces cardiac dysfunction.